2011
DOI: 10.2139/ssrn.1956454
|View full text |Cite
|
Sign up to set email alerts
|

Job Loss Fears and (Extreme) Party Identification: First Evidence from Panel Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Several other studies in economics have used this approach recently, e.g., Geishecker and Siedler (2011), Wunder and Riphahn (2014) and Boll et al (2016) Using the same methods, we also investigated the impact of diabetes on changes in the type of work for those already employed, finding no evidence that diabetes leads to changes in the type of work. These results are also available on request.…”
Section: Duration Of Self-reported Diabetesmentioning
confidence: 99%
“…Several other studies in economics have used this approach recently, e.g., Geishecker and Siedler (2011), Wunder and Riphahn (2014) and Boll et al (2016) Using the same methods, we also investigated the impact of diabetes on changes in the type of work for those already employed, finding no evidence that diabetes leads to changes in the type of work. These results are also available on request.…”
Section: Duration Of Self-reported Diabetesmentioning
confidence: 99%
“…Local labor market shocks Local labor market shocks could increase job insecurity, induce wage freeze or wage cut and might result in job loss, which could influence the political preferences of people. For example Geishecker and Siedler (2011) documents that job loss fears could foster affinity for parties at the far right. Import competition from China increases job insecurity and affects political preferences (Autor et al, 2016;Colantone and Stanig, 2017;Dippel et al, 2015).…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…We complement these studies by exploiting a natural experiment and also by exploring the channels through which a crisis affect political preferences. Papers using survey data (Guiso et al, 2017;Geishecker and Siedler, 2011) measure how economic or job insecurity affect the popularity of populist and far-right parties. The Hungarian setting allows us to study the effect of a well-defined economic shock, which also helps us show that policies promoted by the far-right make these parties popular.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the event of unemployment and populist radical right voting has received more research attention. Many studies on the relationship between unemployment and populist radical right voting show that unemployment and job insecurity are associated with increased support for the populist radical right, both in cross-sectional (Corbetta and Colocca 2013) and longitudinal studies (Geishecker and Siedler 2011;Rink et al 2008). However, some studies have found no relationship (Schmitt-Beck et al 2006) or only for individuals with high levels of political interest (Kohler 2002).…”
mentioning
confidence: 99%